The threat of illegal imports related to narcotics and cosmetics smuggling in the border area of Tarakan: A review from the perspective of national resilience - Surbakti, Yusuf Marsel; Puspitasari, Maria (Indonesian Journal of Multidisciplinary Science, 2024)
The purpose of this study is to identify and analyze the threat of illegal importation, especially the smuggling of narcotics and cosmetics, in the border area of Tarakan, Indonesia. This study adopted a qualitative approach with a case study method, focusing on the operations of Customs during the 2022-2023 period. The analysis of the literature and empirical data obtained through this study revealed that illegal imports pose a number of potential threats that have a significant impact on national security and social and community stability. The vulnerability of unofficial routes and the persistence of illegal activities despite ongoing enforcement measures are the main factors contributing to the success of smugglers' activities. Behavioral analysis of modus operandi reveals that one of the factors that support the successful ssuggling is the cooperation between sggler networks and local communities in border areas. In addition, this study identified several strategic approaches to strengthen surveillance of illegal snugglers, including the use of digital communication tools and new operational strategies, to provide insights for adaptive law enforcement measures. The research provides actionable recommendations for enhancing border security strategies, strengthening inter-agency coordination, and developing targeted policies to mitigate the impact of illegal imported activities on national safety and public welfare.